Outcomes and management of pregnancy in women with bleeding disorder of unknown cause. (21st September 2022) - Castle, Daniel; Desborough, Michael J. R.; Kemp, Michelle; Lowe, Gillian; Thomas, Will; Obaji, Samya
Abstract: Background: Patients with a bleeding tendency with normal laboratory tests have been described as having an unclassified bleeding disorder or bleeding disorder of unknown cause (BDUC). There are very little data available on how to manage pregnancy. Objectives: To study management and outcomes of these patients at four United Kingdom hemophilia comprehensive care centers. Methods: Retrospective case note review from 2010–2020. Results: Sixty deliveries in 36 patients were recorded. The median International Society on Thrombosis and Haemostasis bleeding assessment tool score was 9. In 54 cases for which data were available, the odds ratio for post partum hemorrhage (PPH) was 6.3 for no primary hemostatic prophylaxis versus prophylaxis (95% confidence interval 1.2–34.2, p < .05); 7/9 (78%) versus 16/45 (36%) PPH incidence for the groups, respectively. Hemostatic prophylaxis was with tranexamic acid but some patients received desmopressin or platelet infusions. Secondary PPH was seen in 5/60 (8%) of cases. No neonatal bleeding complications or maternal thromboembolic complications were noted. Avoidance of regional anesthesia and fetal delivery precautions were commonly advised, but in the small number of cases in which they occurred no complications were noted. Conclusions: Despite hemostatic prophylaxis PPH was commonly seen. Further prospective studies of BDUC patients are required to determine optimal management in pregnancy as well as determine the pathophysiological basis of bleeding.